Atributos químicos e físicos de solo sob mata do Jardim Botânico em Goiânia - Mesquita, Glaucia Machado (2014)
In the state of Goiás, its 34 million hectares, only 0.93% represent the Conservation Unit (UCs) full and 2.59% UCs of sustainable use, among these protected areas are the parks. Law Nº. 9985 of July 18, 2000, establishing the National System of Nature Conservation Units (SNUC) is made up of all federal conservation units, state and municipal. This Act establishes criteria and standards for the creation, implementation and management of protected areas. The protected area is the territorial space and its environmental resources, including jurisdictional waters, with relevant natural characteristics, legally instituted by the Government, with conservation objectives and defined limits, under special administration regime, to which adequate safeguards apply to protection. This study aims to evaluate the effect of fire on the chemical and physical properties of soil in a protected area in an urban area, which has preserved area and kills suffered burning process. The study was conducted in the Botanical Garden Amalia Hermano Teixeira (JATH) located in the southern region of Goiânia, Goiás, has a total area of 1,000,000 m2. The soil was classified as Oxisol. In JATH were selected two areas for the study: Burnt Forest (MQ), the area which suffered from illegal burning process in 2010; Preserved forest (MP). Its vegetation is characterized as primary forests have changed, the type Forest Semideciduous. Soil sampling was done at two different times: MQ in September 2012 and MP in May 2013. native forest areas are used as reference areas for soil studies. Thus were estimated physical and chemical indicators of soil penetrometer with up to 40 cm and samples of disturbed and undisturbed soil for the purpose of physical and chemical analysis. Soil samples were collected at depths of 0-5, 5- 10, 10-20 and 20-40 cm. In each area were soil samples collected form a sample grid consists of six rows and five columns with a distance of 10 m between sample points, forming a gride 300 m2. Data were subjected to analysis of variance (ANOVA) and the means were compared within each depth and in each area by 5% Tukey test. The results showed that after four years of the forest burning, observed a concentration of nutrients in the soil profile of MQ in relation to MP at a depth of 0-5 cm. The levels of potassium, calcium and magnesium, present in higher mean values MQ relative to MP, which can be attributed in part to the effect of residual ash. The time after firing do not influence so means the physical soil.